DEVELOPMENT OF MEDIA TRAINER KIT CHARGING SYSTEM TO IMPROVE EFFECTIVENESS AUTOMOTIVE ELECTRICAL PRACTICES - Nurcholish Arifin Handoyono (Universitas Sultan Ageng Tirtayasa, 2019)
The research aims to find out; (1) The process of developing a media trainer kit charging system; (2) The feasibility of the developed media trainer kit charging system; and (3) The effectiveness of the developed media trainer kit charging system. This type of research is a research development using the 4-D model. The research subjects consisted of 20 students, while the object of research was the media trainer kit charging system. Data collection uses observation, questionnaires, and tests. Data were analyzed with descriptive (qualitative and quantitative) and inferential gain test statistics. The results showed that: (1) The process of developing a media trainer kit charging system with a 4-D includes 4 stages, namely define, design, develop, and disseminate; (2) The feasibility test of the media trainer kit charging system by the material expert is 82.5% categorized very good; by the media expert is 81.67% categorized very good; by course lecturer is 72.5% categorized good; by limited trial is 81.25% categorized very good; and extensive trial is 84.62% categorized very good; and (3) The results of the effectiveness test showed that the media trainer kit charging system developed was effectively used in lectures.Keywords: media trainer kit, charging system, automotive electrical